2022
DOI: 10.3390/ijerph192114380
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Culture in Latin American Hospitals: A Systematic Review with Meta-Analysis

Abstract: Introduction: Adverse events in hospitals are prevented through risk reduction and reliable processes. Highly reliable hospitals are grounded by a robust patient safety culture with effective communication, leadership, teamwork, error reporting, continuous improvement, and organizational learning. Although hospitals regularly measure their patient safety culture for strengths and weaknesses, there have been no systematic reviews with meta-analyses reported from Latin America. Purpose: Our systematic review aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 162 publications
(184 reference statements)
3
10
2
1
Order By: Relevance
“…In general, the PS rating valued by professionals was high. This result is consistent with those carried out in other countries such as Ghana [32], and contrary to other studies where the perception is lower, such as those carried out in Latin American countries [37], southwestern Ethiopia [33], Malaysia [38], Iran [39] and national studies [17,28]. The qualification had a significantly higher percentage of positive responses in professionals with time worked in the hospital between 1 and 5 years.…”
Section: Strengthssupporting
confidence: 89%
See 1 more Smart Citation
“…In general, the PS rating valued by professionals was high. This result is consistent with those carried out in other countries such as Ghana [32], and contrary to other studies where the perception is lower, such as those carried out in Latin American countries [37], southwestern Ethiopia [33], Malaysia [38], Iran [39] and national studies [17,28]. The qualification had a significantly higher percentage of positive responses in professionals with time worked in the hospital between 1 and 5 years.…”
Section: Strengthssupporting
confidence: 89%
“…Some investigations show that a lack of knowledge of the registration system may be the main cause of underreporting of incidents [34]. The results of this study add to the already existing knowledge that teamwork and the support of those responsible for units found results in an increase in the notification of incidents and improvement of PS [32,[35][36][37]. In the same way, the number of incidents reported in this hospital is far from the data of national studies, where the majority of respondents did not report any event related to PS in the last year [17,28].…”
Section: Strengthssupporting
confidence: 55%
“…A recent systematic review by Camacho-Rodriguez et al , 9 confirmed the global concern about the PSC in Latin America, revealing that only 30 studies, limited only to five countries (none from Central America), reported a PSC evaluation. Most of these studies are from Brazil (22 studies), 17–38 and only three and one from Colombia 39–41 and Argentina, 42 respectively.…”
Section: Discussionmentioning
confidence: 97%
“…4 The patient safety culture includes risk assessment, preventive and corrective measures, and ongoing development of activities. 5 According to studies, Empowering nurses and supervisors, 6 developing skills in communication, leadership, and teamwork, 7 health policies and their annual assessments, and Staff Well-Being 8 will improve patient safety culture. One of the factors that threaten patient safety is medical errors.…”
Section: Introductionmentioning
confidence: 99%